Ellipticine-loaded apoferritin nanocarrier retains DNA adduct-based cytochrome P450-facilitated toxicity in neuroblastoma cells - Indra, Radek; Černá, Tereza; Heger, Zbyněk; Hraběta, Jan; Wilhelm, Marek; Dostálová, Simona; Lengálová, Alžběta; Martínková, Markéta; Adam, Vojtěch; Eckschlager, Tomáš; Schmeiser, Heinz H; Arlt, Volker M; et al. (Toxicology, 2019)
Although ellipticine (Elli) is an efficient anticancer agent, it exerts several adverse effects. One approach to decrease the adverse effects of drugs is their encapsulation inside a suitable nanocarrier, allowing targeted delivery to tumour tissue whereas avoiding healthy cells. We constructed a nanocarrier from apoferritin (Apo) bearing ellipticine, ApoElli, and subsequently characterized. The nanocarrier exhibits a narrow size distribution suggesting its suitability for entrapping the hydrophobic ellipticine molecule. Ellipticine was released from ApoElli into the water environment under pH 6.5, but only less than 20% was released at pH 7.4. The interaction of ApoElli with microsomal membrane particles containing cytochrome P450 (CYP) biotransformation enzymes accelerated the release of ellipticine from this nanocarrier making it possible to be transferred into this membrane system even at pH 7.4 and facilitating CYP-mediated metabolism. Reactive metabolites were formed not only from free ellipticine, but also from ApoElli, and both generated covalent DNA adducts. ApoElli was toxic in UKF-NB-4 neuroblastoma cells, but showed significantly lower cytotoxicity in non-malignant fibroblast HDFn cells. Ellipticine either free or released from ApoElli was concentrated in the nuclei of neuroblastoma cells, concentrations of which being significantly higher in nuclei of UKF-NB-4 than in HDFn cells. In HDFn the higher amounts of ellipticine were sequestrated in lysosomes. The extent of ApoElli entering the nuclei in UKF-NB-4 cells was lower than that of free ellipticine and correlated with the formation of ellipticine-derived DNA adducts. Our study indicates that the ApoElli form of ellipticine seems to be a promising tool for neuroblastoma treatment.
Keywords: nosiče léků; Apoferritin nanoparticles; Drug Carriers; nádorové buněčné linie; apoferritiny; Nanoparticles; Phosphorylation; Cytochrome P-450 CYP3A; DNA Adducts; Cell Line, Tumor; Drug Compounding; Antineoplastic Agents; Neuroblastoma; Cytotoxicity; DNA adducts; Ellipticines; histony; Ellipticine; Histones; protinádorové látky; Humans; elipticiny; příprava léků; Apoferritins; Cytochrome P450-mediated metabolism; Drug Liberation; viabilita buněk; nanočástice; Cell Survival; uvolňování léčiv; fosforylace; neuroblastom; cytochrom P-450 CYP3A; adukty DNA; lidé